A comparative study of the adoption of public-private partnerships for water services in South Korea and Singapore - Kim, Soojin (2024)
Purpose: This paper investigates the internal factors driving public-private partnership (PPP) adoption for water services in South Korea and Singapore. Design/methodology/approach: This study utilizes a comparative cross-national case study of PPPs in the area of water services by focusing on the similarities and differences between the two countries. Findings: The findings show that while South Korea has employed the PPP model mostly to expand and modernize their sewage systems, Singapore has used PPPs to build and operate desalination facilities that produce potable water through the treatment and filtration of wastewater. The study also demonstrates that fiscal stress and political incentives stemming from socio-economic pressures are the respective critical factors in South Korea and Singapore’s execution of PPP-driven water infrastructure. Originality/value: Through exploring why and how PPPs have been adopted in the specific context, this paper might be helpful to enhance our understanding of the variations and common factors in the policy adoption process within the Asian context.